VALIDATION OF HEUTAGOGY PROBLEM-BASED LEARNING MODEL DEVELOPMENT ASSISTED BY APPLICATION MANAGEMENT SYSTEM - M. Fakhriza , Ganefri, Sukardi , Erwinsyah Simanungkalit , Arfanda AS, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed at developing Problem-Based Learning into application-assisted Heutagogy Problem Based Learning (HPBL). This learning model is based on the concept of self-determined learning and application is the supporting tool helping the students in the self-determined learning process that certainly aims to provide direct experiences and improve the students’ understanding and mastery of the discussion topic for the course of decision support system, thus it is expected that implementing this learning model can improve the students’ competence in problem-solving (Problem Solving Skill). The result of developing the Heutagogy Problem Based Learning model assisted by application management system (HPBL - AMS) in the course of Decision Support System that would be used in conducting learning consisted of 7 (seven) syntax, namely 1), students’ orientation to the problem, 2). Organizing the students, 3). Conducting Web Learning, 4). Defining problems, 5). Alternative Design for ProblemSolving, 6). Problem dissemination, 7). Problem-solving Assessment. The products are in the form of a learning model book, applications, application guide, and learning set that are valid.